2011
DOI: 10.1007/978-3-642-23094-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Curvature Regularization for Curves and Surfaces in a Global Optimization Framework

Abstract: Abstract. Length and area regularization are commonplace for inverse problems today. It has however turned out to be much more difficult to incorporate a curvature prior. In this paper we propose several improvements to a recently proposed framework based on global optimization. We identify and solve an issue with extraneous arcs in the original formulation by introducing region consistency constraints. The mesh geometry is analyzed both from a theoretical and experimental viewpoint and hexagonal meshes are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 15 publications
(33 reference statements)
0
39
0
Order By: Relevance
“…They express that for every edge e only one line pair in the boundary may contain an orientation of e as its first element. Simultaneous to our work appears the work [27] that proposes an alternative constraint system to prevent touching lines. We leave this for future work.…”
Section: Curvature and Linear Programmingmentioning
confidence: 95%
“…They express that for every edge e only one line pair in the boundary may contain an orientation of e as its first element. Simultaneous to our work appears the work [27] that proposes an alternative constraint system to prevent touching lines. We leave this for future work.…”
Section: Curvature and Linear Programmingmentioning
confidence: 95%
“…We will use the pseudo-boolean optimization approach suggested in [5] for an 8-connected grid which requires quartic interactions. The construction can be understood by examining Figure 1.…”
Section: Segmentation With Curvature Regularizationmentioning
confidence: 99%
“…While the runtime for GRD-gen was much faster than GRD it was considerably slower than both of the other methods. The GRD-gen method has potential for this problem but the approximation tightness needs to be improved in order to beat state-of-the-art based on LP relaxations [5]. …”
Section: Segmentation With Curvature Regularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [10], it is shown that Euler's elastica -the line integral of the squared curvature -conforms better to intuitive completion of boundary curves. Other applications where curvature plays an important role include saliency [17], inpainting [9], stereo [21], region-based image segmentation [15] and surface reconstruction [19].…”
Section: Introductionmentioning
confidence: 99%